The Deep Evolutionary Relationships of the Morphologically Heterogeneous Nolinoideae (Asparagaceae) Revealed by Transcriptome Data - Meng, Ran; Luo, Li-Ying; Zhang, Ji-Yuan; Zhang, Dai-Gui; Nie, Ze-Long; Meng, Ying (Frontiers in Plant Science, 2021)
The subfamily Nolinoideae of Asparagaceae is an extremely morphologically heterogeneious group, which is comprised of seven lineages, formerly known as Eriospermaceae, Polygonateae, Ophiopogoneae, Convalariceae, Ruscaceae s.s., Dracaenaceae, and Nolinaceae from different families or even orders. Their drastically divergent morphologies and low level of molecular resolution have hindered our understanding on their evolutionary history. To resolve a reliable and clear phylogenetic relationships of the Nolinoideae, we conducted a comparative transcriptomic study of 15 species representing all the seven lineages. A dataset containing up to 2,850,705 sites across 2126 genes were analyzed using both concatenated and coalescent methods. Except for Eriospermum as outgroup, the transcriptomic data strongly resolved the remaining six lineages into two groups, one is a paraphyletic grade including the woody lineages of dracaenoids, ruscoids, and nolinoids and a monophyletic herbaceous clade. Within the herbaceous group, the Ophiopogoneae + Theropogon is sister to a clade which is composed of Convallarieae and the monophyletic Polygonateae. Our work provides a first robust deep relationship of the highly heterogeneious Nolinoideae and paves the way for further investigations of its complex evolution.